2012
DOI: 10.1089/ars.2011.4221
|View full text |Cite
|
Sign up to set email alerts
|

Production of H2O2 in the Endoplasmic Reticulum Promotes In Vivo Disulfide Bond Formation

Abstract: The results indicate that local H₂O₂ production promotes, while quenching of H₂O₂ impairs disulfide formation. The contribution of H₂O₂ to disulfide bond formation previously observed in vitro can be also shown in cellular and in vivo systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…The threefold increase of the EC 50 value for H 2 O 2 toxicity documents convincingly the high H 2 O 2 inactivation capacity of ER-Catalase N244, also when compared with the overexpression of Prdx4 (Mehmeti et al 2012, Mehmeti et al 2014 or the targeted expression of a WT catalase cDNA in the ER (Margittai et al 2012).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The threefold increase of the EC 50 value for H 2 O 2 toxicity documents convincingly the high H 2 O 2 inactivation capacity of ER-Catalase N244, also when compared with the overexpression of Prdx4 (Mehmeti et al 2012, Mehmeti et al 2014 or the targeted expression of a WT catalase cDNA in the ER (Margittai et al 2012).…”
Section: Discussionmentioning
confidence: 54%
“…However, the fate of the ER-generated H 2 O 2 and its importance for the maintenance of ER homeostasis and oxidative folding efficacy is still unresolved. A number of studies indicate that this luminal H 2 O 2 generation is mandatory for retaining and improving the oxidative protein folding capacity of the ER (Margittai et al 2012, Ramming & Appenzeller-Herzog 2013. This H 2 O 2 is required for the re-oxidation of the reduced PDI protein by ER-localised glutathione peroxidases (GPx7 and GPx8) and potentially also by peroxiredoxin 4 (Prdx4).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Ero1␤-C100A/ C130A also increases the ER glutathione reduction potential as measured by a glutathione-specific fluorescence-based sensor. 7 Similarly, an increased luminal GSSG:GSH ratio has been demonstrated upon stimulation of H 2 O 2 production in the ER by a system based on gulonolactone oxidase (56).…”
Section: Volume 287 • Number 47 • November 16 2012mentioning
confidence: 94%
“…However, it is not clear whether the observed reductive shift is due to activation of the putative transporter responsible for basal GSH uptake or to contribution of alternative transport activities. The observation that luminal hyperoxidation through an Ero1-independent local hydrogen peroxide generation increases the general permeability of the ER membrane seems to support the latter option [45,46].…”
mentioning
confidence: 85%
“…The source of thiol-oxidizing hydrogen peroxide can be the Ero1-catalyzed reaction [32,127]. However, it was also observed that Ero1-independent luminal hydrogen peroxide generation -via gulonolactone oxidase activity -could also stimulate disulfide bond formation [45]. Moreover, hydrogen peroxide itself was able to promote disulfide bond formation, i.e.…”
Section: Formation and Elimination Of Hydrogen Peroxide In The Ermentioning
confidence: 99%